Rejuvenation of Neutrophil Functions in Association With Reduced Diabetes Risk Following Ten Weeks of Low-Volume High Intensity Interval Walking in Older Adults With Prediabetes – A Pilot Study - Bartlett, David B.; Slentz, Cris A.; Willis, Leslie H.; Hoselton, Andrew; Huebner, Janet L.; Kraus, Virginia B.; Moss, Jennifer; Muehlbauer, Michael J.; Spielmann, Guillaume; Muoio, Deborah M.; Koves, Timothy R.; Wu, Helena; et al. (Frontiers in Immunology, 2020)
I have changed the abstract due to reviewers comments, please see attached files